The usefulness of commercial bank portfolio behavior modelling: retrospection and prospects - Σουμπενιώτης, Δημήτριος Ν.; Γεωργόπουλος, Νικόλαος Β.; Πέκκα - Οικονόμου, Βικτωρία (SPOUDAI Journal of Economics and Business, 2001)
The paper aims to develop a methodology for the exploitation of commercial bank's portfolio behaviour models in the implementation of macroeconomic policy. As it has been shown, for the attainment of a chosen set of macroeconomic targets, it can be determined a sufficient, reconstruction of the consolidated commercial banks' portfolio, which, in its turn, can be succeeded in via a large number of alternative government intervention packages. The four successive stages of the methodology comprise: estimation of alternative bank portfolio behaviour models and selection of the prevailing specification; distinction of strategic central government targets that are better explained by the endogenous variables of the prevailing specification; determination of the desired reconstruction in the consolidated banking sector's portfolio, given the desired changes in the macroeconomic targets, and finally; calculation of the alternative central government intervention packages. The empirical demonstration, regarding the Greek case, reveals that such a methodology would be of primary importance for both the policy makers and the monetary authorities of any country. JEL Classification: G21, D78